Project Planning and Field Support for N.O.S. Photobathymetry - Brewer, Ronald K. (The International Hydrographic Review, 2015)
Successful data acquisition for the NOS photobathymetry program is highly dependent on office project planning, scheduling, and field support. Considerable effort is expended prior to the aerial photography phase in developing the horizontal and vertical control specifications, tidal datum requirements, and flight parameters. Specifications for all field support activities are conveyed to the field unit by detailed instructions, job diagrams, and pertinent data collected during the planning phase. Field operations, which include premarking horizontal and vertical control stations and obtaining tidal data, are accomplished in conjunction with the photographic mission and are critical to the success of the data reduction.